2016
DOI: 10.1371/journal.pone.0166154
|View full text |Cite
|
Sign up to set email alerts
|

A Markerless 3D Computerized Motion Capture System Incorporating a Skeleton Model for Monkeys

Abstract: In this study, we propose a novel markerless motion capture system (MCS) for monkeys, in which 3D surface images of monkeys were reconstructed by integrating data from four depth cameras, and a skeleton model of the monkey was fitted onto 3D images of monkeys in each frame of the video. To validate the MCS, first, estimated 3D positions of body parts were compared between the 3D MCS-assisted estimation and manual estimation based on visual inspection when a monkey performed a shuttling behavior in which it had… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
46
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
3
3
2

Relationship

2
6

Authors

Journals

citations
Cited by 39 publications
(46 citation statements)
references
References 47 publications
0
46
0
Order By: Relevance
“…Its technical realization is far from simple, though, especially with the complex movements primates are capable of. When using wireless technology, a desirable approach would be to let the monkey freely decide on their behavior to obtain neural correlates of most natural behavior (Gilja et al, 2010) while motion capture provides the related movement kinematics (Ballesta et al, 2014;Bansal, Truccolo, Vargas-Irwin, & Donoghue, 2012;Nakamura et al, 2016;Peikon et al, 2009). But even if full-body motion capture would be available, it will remain a major challenge to identify to what extent neural activity relates to sensory input, the currently performed movement or the planning of the next movement in free behavior.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Its technical realization is far from simple, though, especially with the complex movements primates are capable of. When using wireless technology, a desirable approach would be to let the monkey freely decide on their behavior to obtain neural correlates of most natural behavior (Gilja et al, 2010) while motion capture provides the related movement kinematics (Ballesta et al, 2014;Bansal, Truccolo, Vargas-Irwin, & Donoghue, 2012;Nakamura et al, 2016;Peikon et al, 2009). But even if full-body motion capture would be available, it will remain a major challenge to identify to what extent neural activity relates to sensory input, the currently performed movement or the planning of the next movement in free behavior.…”
Section: Resultsmentioning
confidence: 99%
“…An alternative are fluorescent or reflective markers directly painted to the skin of the animal (Courtine et al, 2005;Peikon, Fitzsimmons, Lebedev, & Nicolelis, 2009), which also require continuously repeated shaving, or markers that cannot be removed, such as collars (Ballesta, Reymond, Pozzobon, & Duhamel, 2014). A videobased marker-free system using skeleton models was recently reported (Nakamura et al, 2016), however, this or similar systems were not yet reported in a larger, more complex environment with monkeys. We used a commercially available system with only four VGA cameras tracking a permanently dyed part on the animal's fur and the colored cap of the head implant (data not shown).…”
Section: Structured Behavior In the Reach Cage With Macaquementioning
confidence: 99%
“…The high-resolution spatiotemporal data obtained with the markerless motion capture will also aid in understanding brain dynamics underlying the behavior (Berger et al, 2020). Specific posture and motion are informative for studying animals' emotions and intension (Nakamura et al, 2016), and the motor functions (Berger et al, 2020). Furthermore, the automatic and long-term analyses of naturalistic behavior from a large number of subjects permit new data-driven approaches to find unusual behaviors, personalities and, underlying genetic and neural mechanisms (Vogelstein et al, 2014;De Chaumont et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Motion capture technologies allow the quantification of animal's pose and motion with a high spatiotemporal resolution enabling the study of the relationship between various brain functions and behaviors (Vargas-Irwin et al, 2008;Nagasaka et al, 2011;Mathis et al, 2020). However, attaching the physical markers for the motion capture is often not practical for animal studies, as the markers themselves disturb/change the subject's behavior (Nakamura et al, 2016;Mathis et al, 2018;Berger et al, 2020). Thanks to recent advances in machine vision using deep learning, the video-based markerless motion capture has been developed to a level permitting practical use (Mathis et al, 2020), in which an artificial neural network predicts the location of body parts in a video without the requirement for physical markers, and enabled successful behavioral studies in rodents (e.g., Dooley et al, 2020;Cregg et al, 2020;Mathis et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…However, the markers can affect the animals natural behavior. For this reason, lowcost marker-less motion capture systems for animal tracking are developed and introduced in [2] and [3] using depth sensors. Recent studies also utilized convolutional neural networks to do marker-less 2D animal pose estimation such as [5]; however, they have focusd more in laboratory-controlled setups and their results are limited to the fruit fly and mouse.…”
Section: Introductionmentioning
confidence: 99%